PERBEDAAN GAYA KEPEMIMPINAN MANTAN GUBERNUR DKI JAKARTA : BASUKI TJAHAJA PURNAMA (AHOK) VS ANIES BASWEDAN - Yulia Ningsih, Anggun (STKIP Pesisir Selatan, 2023)
This research was conducted with the aim of finding differences between the leadership styles of Ahok and Anies Baswedan when he resigned as Governor of DKI Jakarta, by applying a comparative research method. Sources of data in this study were obtained from primary data through literature studies in various reading sources. Based on the research results, information was obtained that there were significant differences between the two figures in leading the capital city, where Ahok tended to use an authoritarian leadership style and Anies Baswedan applied a more democratic leadership style.